Association Between Lifestyle and Hypertriglyceridemic Waist Phenotype in the PREDIMED‐Plus Study. Issue 3 (24th February 2020) - Fernández‐García, José Carlos; Muñoz‐Garach, Araceli; Martínez‐González, Miguel Ángel; Salas‐Salvado, Jordi; Corella, Dolores; Hernáez, Álvaro; Romaguera, Dora; Vioque, Jesús; Alonso‐Gómez, Ángel M.; Wärnberg, Julia; Martínez, J. Alfredo; Serra‐Majem, Luís; et al.
Abstract : Objective: The hypertriglyceridemic waist (HTGW) phenotype is characterized by abdominal obesity and high levels of triglycerides. In a cross‐sectional assessment of PREDIMED‐Plus trial participants at baseline, HTGW phenotype prevalence was evaluated, associated risk factors were analyzed, and the lifestyle of individuals with metabolic syndrome and HTGW was examined. Methods: A total of 6, 874 individuals aged 55 to 75 with BMI ≥ 27 and < 40 kg/m 2 were included and classified by presence (HTGW + ) or absence (HTGW − ) of HTGW (waist circumference: men ≥ 102 cm, women ≥ 88 cm; fasting plasma triglycerides ≥ 150 mg/dL). Analytical parameters and lifestyle (energy intake and expenditure) were analyzed. Results: A total of 38.2% of the sample met HTGW + criteria. HTGW + individuals tended to be younger, have a greater degree of obesity, be sedentary, and be tobacco users. They had higher peripheral glucose, total cholesterol, and low‐density lipoprotein cholesterol levels; had lower high‐density lipoprotein cholesterol levels; and had increased prevalence of type 2 diabetes mellitus. Mediterranean diet (MedDiet) adherence and physical activity were greater in HTGW − patients. Age, BMI, tobacco use, total energy expenditure, hypertension, type 2 diabetes mellitus, and MedDiet adherence were associated with HTGW + . Conclusions: HTGW is a highly prevalent phenotype in this population associated with younger age, higher BMI, tobacco use, and decreased MedDiet adherence. HTGW − individuals were more physically active with greater total physical activity, and fewer had hypertension.